Korean Drama Addiction and The Quality of Sleep of Indonesian Students - Eka Malfasari; Rizka Febtrina; Rina Herniyanti; Elsi Manda Utari (Indonesian Journal of Global Health Research, 2019)
The current phenomenon is about the addiction of korean drama which has an impact on the quality of students sleep, because students who like korean drama often forget the time to rest and feel curious about of each episode. Sleep is a besic need that must be fulfilled by every individual in order to carry out daily activities properly. The purpose of this research is to find out the relationship between korean drama addiction and the quality of studen’s sleep in STIKes Payung Negeri Pekanbaru. This study was quantitative research with a cross sectional design. The sample of this research as much as 246 students STIKes Payung Negeri Pekanbaru from D3 Midwifery study program as much as 38 students, D3 Nursing as much as 31 students, S1 Nursing as much as 144 students and Public Health S1 as much as 33 students with technique sampling that is stratified random sampling. The instrument of this research used questionnaire compiled by the researchers with 25 statement items obtained from the validity test r result > r table (0,602 > 0,361) and the reliability test result are obtained 0,968. While the sleep quality of questionnaire using Pittsburgh Sleep Quality Indeks (PSQI) which has been translated into indonesian the result of the validity test are obtained 0,365 > 0,361 and reliability 0,741, then the data analysis is tested using chi square. The result of this research found that the majority of students were not addicted to korean drama as much 124 (50,4%) and the majority of poor students sleep quality is 181 (73,6%). The result of this research indicate that there is no relationship between korean drama addiction and quality sleep of studen’s STIKes Payung Negeri Pekanbaru with p value 0,429 > 0,05. Keywords: addicted to korean drama, sleep quality